Sex differences in the relationship between depression and Alzheimer’s disease—mechanisms, genetics, and therapeutic opportunities - Chen, Yu-Han; Wang, Zhi-Bo; Liu, Xi-Peng; Xu, Jun-Peng; Mao, Zhi-Qi (Frontiers in Aging Neuroscience, 2024)
Depression and Alzheimer’s disease (AD) are prevalent neuropsychiatric disorders with intriguing epidemiological overlaps. Their interrelation has recently garnered widespread attention. Empirical evidence indicates that depressive disorders significantly contribute to AD risk, and approximately a quarter of AD patients have comorbid major depressive disorder, which underscores the bidirectional link between AD and depression. A growing body of evidence substantiates pervasive sex differences in both AD and depression: both conditions exhibit a higher incidence among women than among men. However, the available literature on this topic is somewhat fragmented, with no comprehensive review that delineates sex disparities in the depression–AD correlation. In this review, we bridge these gaps by summarizing recent progress in understanding sex-based differences in mechanisms, genetics, and therapeutic prospects for depression and AD. Additionally, we outline key challenges in the field, holding potential for improving treatment precision and efficacy tailored to male and female patients’ distinct needs.